(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: Stroke is one of the main causes of death and neurological disability in Indonesia. Stroke is a cerebrovascular disease which increases in number every year. This study aims to determine the effect of the ratio of Low Density Lipoprotein (LDL) to High Density Lipoprotein (HDL) with the incidence of stroke in the adult population. This study used data from the PTM (non-communicable disease) cohort study in 2011. The sample in this study was adult population (25-65) years who were respondents to the PTM cohort study in Bogor in 2011 which numbered 1506 and analyzed using regression tests. logistics with statistical significance are seen based on 95% confidence intervals. Sample prevalence in adult population in the city of Bogor who suffered a stroke of 1.26%, respondents with a high ratio of LDL to HDL were 35.66%. Respondents with a age of sebesar46 years were 34.26% with the highest prevalence of sex in women amounting to 53.45% and those with low education were 54.58%, respondents who were obese were 27.42%, respondents with high total cholesterol levels were 38, 45% and respondents with high triglyceride levels of 17.07%. The results showed that there was a significant relationship between the ratio of LDL to HDL and the incidence of stroke with an adjusted prevalence odds ratio of 3.909 (95% CI 1.346-11.354). The high ratio of LDL to HDL is at risk for the incidence of stroke in the adult population.